EFEKTIVITAS PROGRAM KERJA DEPARTEMEN PERIBADATAN DAN PENGASUHAN (DEPDATSU) DALAM MENINGKATKAN KEDISIPLINAN SHALAT BERJAMA’AH SANTRI DI PONDOK PESANTREN AL-ITTIFAQIAH INDRALAYA OGAN ILIR - Devi Wulandari; Ismail Sukardi; Abu Mansur (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
The Department of Worship and Care (DEPDATSU) is a sub-section of the extracurricular activities of the Al-Ittifaqiah Islamic Boarding School Islamic Boarding School (OSPI) in Indralaya. Depdatsu has an important role to instill the discipline of students in participating in orderly worship activities. In the midst of the many activities held at the pesantren, there are still a number of students who are not disciplined in attending the prayer activities in the mosque. The purpose of this study is to uncover the effect of the effectiveness of the Depdatsu work program on increasing the discipline of prayer in the congregation of students at the Al-Ittifaqiah Islamic Boarding School Indralaya. This type of research is quantitative descriptive field research (field research). The population was 209 XI MA Al-Ittifaqiah students and 68 students were sampled. Data collection techniques using questionnaires, interviews, observation and documentation. The research data were analyzed using a statistical test with the Product Moment Correlation formula. The results showed that the effectiveness of the Depdatsu work program at Al-Ittifaqiah Islamic Boarding School was included in the moderate category of 48 people (70%) or could be said to be quite effective. While the discipline of prayer in congregation of students at Al-Ittifaqiah Islamic Boarding School is included in the high category of 30 people (44%) or can be said to be very good. Based on the results of hypothesis testing using the product moment formula, it can be seen that at the 5% significance level or the accuracy level of the study of 95%, the value of t_ (count) 6.015> t_table 1.998 means the alternative hypothesis is accepted and the null hypothesis is rejected. Thus it can be concluded that there is a significant effect on the effectiveness of the Depdatsu work program on improving the discipline of the santri congregational prayer at Al-Ittfaqiah Islamic Boarding School Indralaya